Control previo y gestión de tesorería en la Municipalidad Provincial de Requena, 2023 - Talexio Flores, Nair Idania (2024)
The final report presents a main objective of determining the relationship between prior control and treasury management in the Provincial Municipality of Requena 2023, where a population of 60 administrative workers was taken to whom a questionnaire of questions was used to collect of data. The results showed that prior control is classified as regular (28%), because prior authorization is granted for greater supervision services in cases other than additional work, the documentation supporting the operations that involve the credit of the entity and prior binding opinions are issued in internal contracts exempt from public tenders. As for treasury management, it has a regular rating (28%) since sometimes deposit registrations are made on the same day. However, the accrual phase of each file is always reviewed and controlled and delays in payment to suppliers, workers and officials are avoided. Achieving determines that there is a positive relationship between prior control and treasury management, corroborated by a coefficient of 0.787 and a significance value of 0.000.